2020
DOI: 10.1186/s12995-020-00265-0
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of occupational injury and its associated factors in Ethiopia: a systematic review and meta-analysis

Abstract: Background: Occupation related fatality and mortality rate is becoming the devastating issue globally as reported by the International Labor Organization (ILO). Though there are reports about exposure and burden of occupational injury from the regional states, the studies were fragmented and inconclusive ones at the national level. Hence, the authors' intention being to come up with the national pooled estimates of occupation related injury and the associated factors in Ethiopia. Methods: The international rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 51 publications
4
32
3
Order By: Relevance
“…In this study, the prevalence of upper back pain was 53.5% (49.42–57.46) which was higher than the study conducted in Bangladesh (38%), Nepal (7.5%), and Taiwan (32.7%) [ 19 , 23 , 30 ], respectively. The possible reason might be due to the difference in the study participants, sociodemographic characteristics, and differences in workload.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…In this study, the prevalence of upper back pain was 53.5% (49.42–57.46) which was higher than the study conducted in Bangladesh (38%), Nepal (7.5%), and Taiwan (32.7%) [ 19 , 23 , 30 ], respectively. The possible reason might be due to the difference in the study participants, sociodemographic characteristics, and differences in workload.…”
Section: Discussioncontrasting
confidence: 74%
“…e prevalence of elbow and wrist pain was 53.8% (49.76%-57.79%) and 51.6% (47.56-55.62), respectively. is study was higher than the study conducted among restaurant workers in Taiwan (27.3%) and Nepal (5%) and hotel housekeeping in Gondar town (47.2%) and barbers in Gondar town (29.3%) [19,[30][31][32], respectively. e possible explanation could be the restaurant workers' tasks require repetitive and forceful movement of the hand as compared e difference in socioeconomic and working processes in the study area and Taiwan is quite different.…”
Section: Discussioncontrasting
confidence: 64%
“…This is similar to other studies that showed the manufacturing and construction sectors had the highest cases of injuries. [44][45][46] Data gathered for this review were taken from different government and non-government agencies and spans from 2011 to 2017. However, the Republic Act 11058 or "An Act Strengthening Compliance with Occupational Safety and Health Standards and Providing Penalties for Violations Thereof " was signed into law in 2018, which is a year not covered in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In Ethiopia, reports indicated that only 5 to 10% of workers have access to occupational health services in their respective workplaces [7]. But nearly half [44.66%] of the workers in Ethiopia were experienced occupational injury.…”
Section: Introductionmentioning
confidence: 99%
“…But nearly half [44.66%] of the workers in Ethiopia were experienced occupational injury. Upon reviewing several literatures about occupational health and safety among factory workers for this study, the PPE utilization rate typically ranges between 20.6% and 82.4% [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%